Lens vault, thickness, and position in Chinese subjects with angle closure - Nongpiur, Monisha E; He, Mingguang; Amerasinghe, Nishani; Friedman, David S; Tay, Wan-Ting; Baskaran, Mani; Smith, Scott D; Wong, Tien Yin; Aung, Tin (Ophthalmology (Rochester, Minn.), 2011)
To investigate the association of lens parameters-specifically, lens vault (LV), lens thickness (LT), and lens position (LP)-with angle closure. Prospective, comparative study. One hundred two Chinese subjects with angle closure (consisting of primary angle closure, primary angle-closure glaucoma, and previous acute primary angle closure) attending a glaucoma clinic and 176 normal Chinese subjects with open angles and no evidence of glaucoma recruited from an ongoing population-based cross-sectional study. All participants underwent gonioscopy and anterior-segment optical coherence tomography (AS OCT; Carl Zeiss Meditec, Dublin, CA). Customized software was used to measure LV, defined as the perpendicular distance between the anterior pole of the crystalline lens and the horizontal line joining the 2 scleral spurs, on horizontal AS OCT scans. A-scan biometry (US-800; Nidek Co, Ltd, Tokyo, Japan) was used to measures LT and to calculate LP (defined as anterior chamber depth [ACD] +1/2 LT) and relative LP (RLP; defined as LP/axial length [AL]). Lens parameters and angle closure. Significant differences between angle-closure and normal eyes were found for LV (901±265 vs. 316±272 μm; P<0.001), LT (4.20±0.92 vs. 3.90±0.73 mm; P = 0.01), LT-to-AL ratio (0.18±0.04 vs. 0.16±0.03; P<0.001), ACD (2.66±0.37 vs. 2.95±0.37 mm; P<0.001), and AL (22.86±0.93 vs. 23.92±1.37 mm; P<0.001), but no significant differences were found for LP (4.76±0.51 vs. 4.90±0.54 mm; P = 0.34) or RLP (0.21±0.02 vs. 0.20±0.02; P = 0.14). After adjusting for age, gender, ACD, LT, and RLP, increased LV was associated significantly with angle closure (odds ratio [OR], 48.1; 95% confidence interval [CI], 12.8-181.3, comparing lowest to highest quartile), but no association was found for LT (OR, 1.78; 95% CI, 0.76-4.16), LP (OR, 1.94; 95% CI, 0.59-6.31), or RLP (OR, 2.08; 95% CI, 0.66-6.57). There was low correlation between LV and LT (Pearson's correlation coefficient [PCC], 0.17), between LV and RLP (PCC, 0.08), or between LV and LP (PCC, 0.2). Eyes with angle closure have thicker lenses with greater LV compared with normal eyes. The LV, which represents the anterior portion of the lens, is a novel parameter independently associated with angle closure after adjusting for age, gender, ACD, and LT.